Three-Dimensional Printing of a Container Tablet: A New Paradigm for Multi-Drug-Containing Bioactive Self-Nanoemulsifying Drug-Delivery Systems (Bio-SNEDDSs) - Vineet R. Kulkarni; Mohsin Kazi; Ahmad Abdul-Wahhab Shahba; Aakib Radhanpuri; Mohammed Maniruzzaman (MDPI AG, 2022)
This research demonstrates the use of fused deposition modeling (FDM) 3D printing to control the delivery of multiple drugs containing bioactive self-nano emulsifying drug-delivery systems (SNEDDSs). Around two-thirds of the new chemical entities being introduced in the market are associated with some inherent issues, such as poor solubility and high lipophilicity. SNEDDSs provide for an innovative and easy way to develop a delivery platform for such drugs. Combining this platform with FDM 3D printing would further aid in developing new strategies for delivering poorly soluble drugs and personalized drug-delivery systems with added therapeutic benefits. This study evaluates the performance of a 3D-printed container system containing curcumin (CUR)- and lansoprazole (LNS)-loaded SNEDDS. The SNEDDS showed 50% antioxidant activity (IC50) at concentrations of around 330.1 µg/mL and 393.3 µg/mL in the DPPH and ABTS radical scavenging assay, respectively. These SNEDDSs were loaded with no degradation and leakage from the 3D-printed container. We were able to delay the release of the SNEDDS from the hollow prints while controlling the print wall thickness to achieve lag phases of 30 min and 60 min before the release from the 0.4 mm and 1 mm wall thicknesses, respectively. Combining these two innovative drug-delivery strategies demonstrates a novel option for tackling the problems associated with multi-drug delivery and delivery of drugs susceptible to degradation in, i.e., gastric pH for targeting disease conditions throughout the gastrointestinal tract (GIT). It is also envisaged that such delivery systems reported herein can be an ideal solution to deliver many challenging molecules, such as biologics, orally or near the target site in the future, thus opening a new paradigm for multi-drug-delivery systems.